Relationship between genetic variability of flowering traits and Fusarium mycotoxin contamination in oats. Issue 2 (16th March 2020) - Herrmann, Matthias Heinrich; Hautsalo, Juho; Georgieva, Paulina; Bund, Adalbert; Winter, Mark; Beuch, Steffen
Abstract: Over the last three decades, Fusarium infections and related mycotoxin contamination have caused significant economic losses in oats ( Avena sativa L.). Breeding for resistance is highly prioritized in oats, but infection processes and resistance components against Fusarium species are not fully identified. In this study, the genetic variation for flowering traits and its impact on mycotoxin accumulation in oats is described. The first experiment of this paper was focused on flowering traits in 50 oat genotypes (Panel 1) to identify cleistogamic oats. Then, two separate Fusarium ‐inoculated experiments in three (Panel 2 with 25 genotypes) and two environments (Panel 3 with 16 genotypes) were conducted to assess the relationship between the degree of anther retention (AR) and resistance to Fusarium infestation and mycotoxin accumulation in oats. Panel 2 was inoculated with Fusarium culmorum, F. langsethiae, and F. sporotrichioides, and Panel 3 was inoculated with either F . graminearum or F. culmorum . The assessment of open flowering score and AR displayed a continuous variation from dominating chasmogamy to complete cleistogamy. Significant differences for deoxynivalenol and T‐2 were found, with a modest correlation between both mycotoxins. The lowest mycotoxin levels were found in two old and one modern cultivar, and the highest levels were found in a dwarf oat cultivar. Compared with plant height, AR was a rather ambiguous factor for the mycotoxin content, and it interfered with effects of other traits displaying high ranges such as earliness, lodging, or hull content. To unravel components of resistance to Fusarium in oats more precisely, specific populations with lower ranges in plant height and heading date should be studied.